Hambatan-Hambatan Mewujudkan Pemilu Inklusif bagi Penyandang Disabilitas pada Pemilu Kota Surabaya: Studi di Kecamatan Sukomanunggal - Mezaluna Indy Permatasari (Jurnal Politik Indonesia, 2023)
Inclusive elections involve diverse identities, including gender, minority groups, marginalized groups, and groups with disabilities. These elections provide special access for blind voters, including data collection and voting facilities at their residences, familiarization with special materials, accessible polling stations, and accessible voting equipment. The 2019 Surabaya City Election in Sukomanunggal District was not inclusive due to structural obstacles such as not verifying data on persons with disabilities, not providing outreach to every residence, and not using special outreach materials for disabilities. The research method used was field study, collecting data through in-depth interviews and documentation. The theoretical perspective of inclusive elections was used to analyze the results, revealing that the 2019 Surabaya City Election in Sukomanunggal District was not inclusive. Cultural barriers arose due to the lack of voting facilities for blind voters, leading to despair and a belief that their participation will not have any impact on the election. Additionally, their families did not allow them to attend the polling stations.